2021
DOI: 10.3390/plants10020326
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Different Vegetal-Derived Protein Hydrolysates Distinctively Modulates Tomato Root Development and Metabolism

Abstract: Despite the scientific evidence supporting their biostimulant activity, the molecular mechanism(s) underlying the activity of protein hydrolysates (PHs) and the specificity among different products are still poorly explored. This work tested five different protein hydrolysates, produced from different plant sources using the same enzymatic approach, for their ability to promote rooting in tomato cuttings following quick dipping. Provided that all the different PHs increased root length (45–93%) and some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 55 publications
4
45
0
1
Order By: Relevance
“…3 The effect of seed priming with aqueous duckweed extracts on a leaf area and b chlorophyll content in maize at 21 DAS. Letters, if different, indicate statistically significant differences for P < 0.05 between treatments (n = 3) line with previous studies on other plant-based biostimulants (Ceccarelli et al 2021).…”
Section: Discussionsupporting
confidence: 89%
“…3 The effect of seed priming with aqueous duckweed extracts on a leaf area and b chlorophyll content in maize at 21 DAS. Letters, if different, indicate statistically significant differences for P < 0.05 between treatments (n = 3) line with previous studies on other plant-based biostimulants (Ceccarelli et al 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Three of them were commercial products obtained by thermal-chemical hydrolysis of animal-derived proteins [Siapton ® (I) commercialized by Sumitomo Chemical Italia S.r.l., Milano, Italy] or enzymatic hydrolysis of vegetal-derived proteins [Trainer ® (D), and Vegamin ® (H) commercialized by Hello Nature Inc. (former Italpollina), Anderson, IN, United States]. The other eight PHs were obtained from vegetal proteins by enzymatic hydrolysis as described previously ( Colantoni et al, 2017 ; Ceccarelli et al, 2021 ). Plant biomass from Fabaceae (A, G, O), Malvaceae (C), Brassicaceae (F), Solanaceae (B), and Graminaceae (E, P) were used as protein sources for the other eight PHs.…”
Section: Methodsmentioning
confidence: 99%
“…Other application of protein hydrolysates refer to plants subjected to stress conditions such as in the study of Koleška et al [ 136 ] who tested the effectiveness of biostimulants in alleviating macronutrient deficiency effects on tomato plants, or Casadesús et al [ 137 ] and Ertani et al [ 138 ] who studied the hormonal effects of plant biostimulants on water-stressed tomato plants. It is suggested that foliar or root applications of protein hydrolysates may improve root development, C and N assimilation and nutrients uptake from plants [ 33 , 139 , 140 ], regulate the metabolic processes through a multi-level signaling that involves auxin-like activities [ 141 , 142 , 143 ], as well as to increase the effectiveness of plant defense mechanisms against abiotic stressors in a sustainable manner [ 144 ]. However, apart from increased tolerance to stressors the application of protein hydrolysates may enhance quality parameters in fruit and leafy vegetables [ 35 , 105 , 145 ].…”
Section: Practical Applications Of Biostimulants and Biostimulatory Products On Horticultural Cropsmentioning
confidence: 99%